BOOK REVIEW OF THE CLOCKWORK THREE WRITTEN BY MATTHEW J KIRBY - Novrianto, Andri (LANTERN (Journal on English Language, Culture and Literature), 2016)
Literature is the piece of writing valued as a work of art, especially novels, plays and poems. Novel is one of literary works that tell the reader a story which consist of plot, character, theme and conflict.Novel also has many themes such as Romance, Heroic and Friendship. Many authors use friendship as the main theme in literary works. One of thoseis depicted in Matthew J Kirby’s The Clockwork Three.